1994
DOI: 10.1002/jmv.1890430219
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA and anti‐HPV secretory IgA antibodies in cytologically normal cervical specimens

Abstract: Cervical specimens collected from 163 cytologically healthy women were screened for the presence of human papillomavirus (HPV) DNA and anti-HPV secretory IgA antibodies. HPV DNA was detected by a general primer mediated polymerase chain reaction (PCR), which amplifies a conserved region from the L1 ORF of genital HPVs. The PCR products were typed by restriction enzyme digestion. A total of 35 samples (21.5%) were positive for HPV DNA (13 samples for HPV 6, 6 for HPV 16, 3 for HPV 18, and 13 for untypeable HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
0
26
0
3
Order By: Relevance
“…In general, most of these women had been infected with HPV at some point during their early adult life when sexual activity began [9]. As the age of exposure to these genital HPV types should be similar, the current data may suggest that the duration from primary HPV infection to the development of cervical cancer is possibly shorter for HPV-18.…”
Section: Discussionmentioning
confidence: 86%
“…In general, most of these women had been infected with HPV at some point during their early adult life when sexual activity began [9]. As the age of exposure to these genital HPV types should be similar, the current data may suggest that the duration from primary HPV infection to the development of cervical cancer is possibly shorter for HPV-18.…”
Section: Discussionmentioning
confidence: 86%
“…In other studies from Central European countries, HPV-16 has been detected in 0-7% and HPV-18 in 0-2.3% of normal cervices, but less sensitive HPV detection methods were used in those studies [Czegledy et al, 1989[Czegledy et al, , 1993Mincheva et al, 1991]. One study that used a comparable general-primermediated method showed a prevalence of HPV-16 in 3.7% and HPV-18 in 1.8% of normal cervices [Veress et al, 1994].…”
Section: Discussionmentioning
confidence: 94%
“…This relation and the observation that HPV-infected tissue does not always show cytological abnormalities [Lambropoulos et al, 1994;Veress et al, 1994; DeVilliers et al., 19871 make it necessary to detect the HPV by mo-…”
mentioning
confidence: 89%